Contributions of Muslim scholars attributed to other scholars in optics - Banu, Asfana; Shuriye, Abdi Omar (Center for Promoting Ideas, 2017)
IbnSahl, a Muslim scholar during the Golden Age in the history of Islam, had contributed in developing of the Snell’s law. He explained the law in his book entitled On the Burning Instrument (Kitab al-Parraqat) which was written in 984 CE. Similarly, the first ever camera was developed by Ibn Al-Haytham, a Muslim scholar. Camera obscura which was one of his famous inventions developed based on the idea that was initiated by observing the dust particles found in a stream of light. In addition, telescope and microscope development also should be credited to Ibn Al-Haytham since he was the first scholar who managed to identify the refraction and reflection of light theory. Based on the theory, concave and convex lenses were developed which later became the basic foundation to construct the telescope and microscope.